Morphological issues in Risalah al-Sahil and al-Shahej by Abu Ala Al-Maari - Abdulhassan Ajeel, Sawsan (Journal of College of Education, 2020)
This research represents an attempt to monitor morphological issues in the letter of Al-Sahil and Al-Shahej by Abu Al-Ala Al-Maari and to state his opinion on it. The most embarrassing and ambiguous era for the Islamic nation was a dialogue between the Sahih, who is the Persians, and the Shahej, who is the donkey, so he conveyed what was going on in his mind through their lips. The message was full of various morphological issues, and we divided the research on its basis, some of which were related to nouns as the statement of the origin of (al-Atharib) and the derivation of the subject’s name from the non-triple and the difference between the habala and the habala and others, and some of them concerned the verbs such as the statement of the origin of the lam in the verb (Ola), and the difference between (whole and all) ) And the difference between (a stick, a stick and a stick), and some of them are common between nouns and verbs such as al-Ialin in homogeneous buildings, the lack of two heels in a single word, and the places of the heart of the wav. Most of the morphological issues mentioned by Al-Maarri were in agreement with what was mentioned by Arab scholars who were before him and those who came after him, but there are some issues that are contrary to that. These issues revealed the interest of Al-Maarri and his interest in clarifying the intent of his questions, as he used to multiply and diversify examples and evidence in addition to the diversity of his methods in presenting the material in a way that guarantees the best performance of the idea, and uses the method of asking questions and then answering them. We often found Al-Maarri in this letter trying to link the sciences of Arabic with each other, as well as linking it to other sciences such sciences, sociology and others.